Impact of sunlight on chloramphenicol mediated synthetic and herbal eye drops in terms of antimicrobial activity - Mazumder, Permita (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.